The Amount of Support Provided by a Passive Arm Support Exoskeleton in a Range of Elevated Arm Postures - de Vries, Aijse; Murphy, Molly; Könemann, Reinier; Kingma, Idsart; de Looze, Michiel (IISE transactions on occupational ergonomics and human factors, 2019)
Our study quantified the extent of support provided by a passive arm-support exoskeleton throughout a range of postures. Mechanical support generated by the arm-support exoskeleton (SkelEx, Rotterdam, The Netherlands) that we tested clearly reaches its maximum at elevation angles ranging from 60° to 120°, where the required support is also highest. In contrast, for elevation angles below 30°, this exoskeleton provided significantly less support. Depending on the task, other support characteristics might be required. These results may help practitioners who are considering the adoption of an exoskeleton in the workplace. We advocate adapting mechanical support settings or effective range to the actual specific working envelope of postures. Background: The use of arm-support exoskeletons is an emerging strategy to mechanically support workers during elevated arm tasks. In the present study, we evaluated the effects of wearing a passive exoskeleton on the shoulder moment and on the activity of six muscles in the shoulder region, in a range of elevated arm postures. Methods: Twelve participants were asked to maintain 15 static arm positions, which were combinations of different vertical elevations and horizontal abductions, both with and without the exoskeleton. The postures were composed of five elevation angles (vertical elevation: 30°-150°) and three horizonal abduction angles (HAb: 0°-60°). During the static postures, we obtained the supportive moment provided by the exoskeleton by measuring the interaction force, as well as muscle activity via electromyography of six relevant muscles: deltoid anterior, deltoid posterior, upper trapezius, lower trapezius, latissimus dorsi, and biceps brachii. We compared the moment that was required from the subjects to maintain the arm postures, as well as the muscle activity, between conditions with and without exoskeleton. Results: The supportive moment provided by the exoskeleton (0.5-6.1 Nm; up to 56% of the required moment) implied a significant reduction to the shoulder moment that needed be generated by the subject. These effects were dependent on the arm posture, though, particularly on the vertical arm elevation angle rather than horizontal abduction. Mechanical support was highest at the vertical elevation angles that were most demanding (90° and 120°). This effect caused the required moment from the subject to be relatively consistent across different shoulder angles. Muscle activity was reduced in three of the six muscles (deltoid anterior, upper trapezius, and latissimus dorsi). However, for two muscles (upper trapezius and lower trapezius), the effects were dependent on the vertical arm elevation angle and an increase in muscle activity was evident for the lower trapezius at vertical elevation 150°. Conclusion: Our results emphasize the importance of analyzing the task demands, such as working posture, when selecting or designing arm support exoskeletons.